2013
DOI: 10.1098/rsbl.2013.0383
|View full text |Cite
|
Sign up to set email alerts
|

Developing ultraviolet illumination of gillnets as a method to reduce sea turtle bycatch

Abstract: Fisheries bycatch of marine animals has been linked to population declines of multiple species, including many sea turtles. Altering the visual cues associated with fishing gear may reduce sea turtle bycatch. We examined the effectiveness of illuminating gillnets with ultraviolet (UV) light-emitting diodes for reducing green sea turtle (Chelonia mydas) interactions. We found that the mean sea turtle capture rate was reduced by 39.7% in UV-illuminated nets compared with nets without illumination. In collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 17 publications
(48 reference statements)
2
63
1
1
Order By: Relevance
“…Our results indicate that Sechura Bay is an important foraging area and developmental habitat for green turtles and also possibly for critically endangered hawksbill turtles. This research found that a majority of sets having bycatch, given these catch rates; we recommend the identification and implementation of mitigation measures to reduce sea turtle bycatch, like illuminating nets with LED lights, shark silhouettes and use float lines without buoys (Gilman et al, 2010;Wang et al, 2010Wang et al, , 2013Ortiz et al 2016). To help maximize their uptake and effectiveness, such efforts to identify solutions should involve small-scale 611 Incidental capture of sea turtles in Sechura Bay, Peru 7 fishermen as well as scientists and other stakeholders and decision-makers.…”
Section: Conclusion and Recommendationsmentioning
confidence: 80%
See 3 more Smart Citations
“…Our results indicate that Sechura Bay is an important foraging area and developmental habitat for green turtles and also possibly for critically endangered hawksbill turtles. This research found that a majority of sets having bycatch, given these catch rates; we recommend the identification and implementation of mitigation measures to reduce sea turtle bycatch, like illuminating nets with LED lights, shark silhouettes and use float lines without buoys (Gilman et al, 2010;Wang et al, 2010Wang et al, , 2013Ortiz et al 2016). To help maximize their uptake and effectiveness, such efforts to identify solutions should involve small-scale 611 Incidental capture of sea turtles in Sechura Bay, Peru 7 fishermen as well as scientists and other stakeholders and decision-makers.…”
Section: Conclusion and Recommendationsmentioning
confidence: 80%
“…Sea turtle bycatch per unit effort (CPUE) was determined as: CPUE = number of turtles captured / (net length [km]) × (soak time of net [12 h]) (Wang et al, 2013). Gillnet bycatch data for the study was grouped by month in order to derive monthly stratified CPUE estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perbandingan hasil tangkapan bycatch penyu dan tangkapan HTU dihitung berdasarkan catch per unit effort (CPUE). CPUE merupakan nilai estimasi laju tangkapan setiap ulangan dibagi dengan tingkat upaya yang telah distandarisasi, setiap panjang jaring 1 km dan waktu perendaman 12 jam atau (km x 12 jam) -1 (Wang et al 2013). Hal ini digunakan agar perbandingan antara gillnet kontrol dan gillnet eksperimen dalam upaya yang sama.…”
Section: Analisis Pengaruh Penggunaan Lampu Led Hijau Terhadap Bycatcunclassified